IMPLEMENTATION OF BILATERAL FILTERING FOR AESTHETIC ENHANCEMENT OF FACIAL IMAGES - Wijaya, Ardi; Febriani, Lovi; Muntahanah, Muntahanah; Veronika, Nuri David Maria (Institut Bakti Nusantara, 2025)
Digital image is a representation of an image in the form of pixels arranged in a matrix. The image processing process includes acquisition, analysis, and manipulation to produce the desired output. In photography and social media, digital images play an important role in attracting attention. However, photos often experience problems such as noise and uneven lighting, which can reduce image quality. Therefore, image enhancement is needed to overcome these problems. The Bilateral Filtering method is one of the techniques that is very effective in reducing noise by considering the special distance and intensity differences between pixels, so that it can maintain the clarity of important elements in the image. This study aims to implement this technique in improving the aesthetics of facial images and evaluate its effectiveness in producing more attractive and high-quality images. from 50 datasets taken. The results of the study showed that Bilateral Filtering was able to improve the clarity of facial images without eliminating important details. The evaluation was carried out using image quality parameters such as PSNR (Peak Signal-to-Noise Ratio) and SSIM (Structural Similarity Index), which showed an increase in quality after the application of this method. In terms of user satisfaction, the results of the questionnaire showed that the satisfaction level reached 86.38%, which based on Table 5 is included in the